Intake of Wild Blueberry Powder Improves Episodic-Like and Working Memory during Normal Aging in Mice - Beracochea, Daniel; Krazem, Ali; Henkouss, Nadia; Haccard, Guillaume; Roller, Marc; Fromentin, Emilie (Planta Medica, 2016)
The number of Americans older than 65 years old is projected to more than double in the next 40 years. Cognitive changes associated to aging can affect an adultʼs day-to-day functioning. Among these cognitive changes, reasoning, episodic memory, working memory, and processing speed decline gradually over time. Early memory changes include a decline in both working and episodic memory. The aim of the present study was to determine whether chronic (up to 75 days) daily administration of wild blueberry extract or a wild blueberry full spectrum powder would help prevent memory failure associated with aging in tasks involving various forms of memory. Both blueberry ingredients were used in a study comparing young mice (6 months old) to aged mice (18 months old). At this age, mice exhibit memory decline due to aging, which is exacerbated first by a loss in working and contextual (episodic-like) memory. Contextual memory (episodic-like memory) was evaluated using the contextual serial discrimination test. Working and spatial memory were evaluated using the Morris-Water maze test and the sequential alternation test. Statistical analysis was performed using an ANOVA with the Bonferroni post-hoc test. Supplementation with wild blueberry full spectrum powder and wild blueberry extract resulted in significant improvement of contextual memory, while untreated aged mice experienced a decline in such memory. Only the wild blueberry full spectrum powder significantly contributed to an improvement of spatial and working memory versus untreated aged mice. These improvements of cognitive performance may be related to brain oxidative status, acetylcholinesterase activity, neuroprotection, or attenuation of immunoreactivity.
Keywords: wild blueberry; episodic memory; working memory; aging; serial contextual discrimination; alternation